Role of Social Media in Cultivating Brand Loyalty among Millennials and Gen Z (International Journal of Food and Nutritional Sciences, 2022)
Social media advertising is a novel approach to brand or goods advertising, aimed at cultivating afavourable public opinion and encouraging brand loyalty. This research looks at how loyalty tobrands among millennials and Generation Z—a group that is highly engaged with technologiesand social media—is affected by social media influencers. The research applied different users ofInstagram from Indonesia and made a route analysis and Sobel investigated to look at the indirectimpact. Testing for accuracy, dependability, and traditional presumptions was performed to ensurethe information was suitable for extra examination. The findings highlighted that buying intentionsmay act as a mediating factor between social media experts and Millennial devotion to brands, aswell as the way social platform influences can affect Generation Z and millennials’ loyalty to abrand. This study emphasizes how crucial it is to develop promotional strategies that work withmillennials and Generation Z.